Consumption habits of broiler offal and its contamination by antibiotic residues in the Northeast of Algeria - Kadi, Hanane; Boudebza, Assia; Abdeldjelil, Mohamed Cherif; Boultif, Latifa; Mansour, Fadhila; Chougui, Ismail; Douak, Quamar Eddine; Elmechta, Lamia (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Antibiotic use has promoted poultry production intensification. However, irrational use of these drugs results in an accumulation of toxic and harmful residues in the edible products of the treated birds. These residues eventually affect the consumer’s health by transferring antibiotic–resistant bacteria and causing allergies and other pathologies. This study aims to describe the consumption habits of broiler offal in two Algerian Provinces: Batna and Sétif (North–East of Algeria). In addition, a qualitative study was conducted to screen antibiotic residues in broiler offal commercialized in these regions. A total of 250 consumers were randomly surveyed using a questionnaire including questions regarding their socio–demographics, their consumption habits of offal, and their knowledge of the risks associated with the presence of antibiotic residues in poultry products. The study was conducted from 5th February to 25th March 2019. Antibiotic residues were investigated in 66 broiler samples (36 livers and 30 gizzards) using an agar diffusion test inspired by the conventional microbiological method of the four plates. The survey revealed high consumption rates of offal: 83.3% in Batna and 92.0% in Sétif. The liver was the most preferred offal in both regions due to its palatability (86.5%) and nutritional value (67.3%). Most respondents (68% in Batna and 52% in Sétif) are aware of the risks of antibiotic residues in offal. The results of the antibiotic residue investigation showed an overall contamination rate of 33.3%. Livers were more contaminated than gizzards. In both regions, the widespread consumption of broiler offal and its contamination by antibiotic residues constitute a potential health hazard for consumers.